2013
DOI: 10.3390/pathogens2020383
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Therapeutic Treatments against Burkholderia Infections Using Imaging Techniques

Abstract: Burkholderia mallei, the etiologic agent of glanders, are Category B select agents with biothreat potential, and yet effective therapeutic treatments are lacking. In this study, we showed that CpG administration increased survival, demonstrating protection in the murine glanders model. Bacterial recovery from infected lungs, liver and spleen was significantly reduced in CpG-treated animals as compared with non-treated mice. Reciprocally, lungs of CpG-treated infected animals were infiltrated with higher levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In the study by Judy, et al ., a moderate pro-inflammatory response was associated with protection while excessive inflammation caused pulmonary pathology [ 26 ]. Further, the protective effects of CpG treatment to reduce lung pathology were attributed to a reduction in neutrophil and inflammatory monocyte recruitment [ 26 , 50 ]. Similarly, we have previously shown that the virulence of B .…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Judy, et al ., a moderate pro-inflammatory response was associated with protection while excessive inflammation caused pulmonary pathology [ 26 ]. Further, the protective effects of CpG treatment to reduce lung pathology were attributed to a reduction in neutrophil and inflammatory monocyte recruitment [ 26 , 50 ]. Similarly, we have previously shown that the virulence of B .…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, FPR1 has demonstrated high specificity and affinity to a synthetic hexapeptide, cinnamoyl‐F‐(D)L‐F‐(D)L‐F (cFLFLF), which was utilized to deliver various payloads to different septic and sterile inflammatory loci for imaging purposes by us and others . For example, we have reported the application of a near infrared fluorescent (NIRF) probe, cFLFLF‐poly(ethylene glycol) ‐cyanine 7 (cFLFLF‐PEG‐Cy7) and a positron emission tomography (PET) probe, cFLFLF‐PEG‐ 64 Cu for non‐invasive imaging of inflammation with different animal models.…”
mentioning
confidence: 99%
“…The spread of both wild type and capsule mutant strains of B. pseudomallei has been compared in the BALB/c mouse model with an immunocompentent, hairless SKH-1 mouse strain, that is, particularly useful for FL imaging studies due to low autofluorescent background usually generated by fur. Infection studies with a BL strain of B. mallei have also been reported [150,151] with a BL signal detectable in the lung after i.n. challenge from 48 h after infection (p.i.…”
Section: Biphotonic Imagingmentioning
confidence: 94%
“…This mouse model of B. mallei infection has been further used to investigate the effects of CpG treatment alone, previously shown to provide protection against B. mallei infection when given preexposure to mice [152]. Mott et al (2013) [151] used dual signal imaging to elucidate the role of CpGs on neutrophil activation using a neutrophil-specific fluorescent probe. This cyanine 7-conjugate, PEG modified hexapeptide reagent specifically binds to the formylpeptide receptor of neutrophils [136].…”
Section: Biphotonic Imagingmentioning
confidence: 99%